Estudo comparativo in vitro da resistência ao cisalhamento de sistemas adesivos em dentina humana: uso de hipoclorito de sódio em sistemas convencionais ou primers acidificados - Pucci, Cesar Rogério [UNESP] (Universidade Estadual Paulista (Unesp), 2002)
The aim of this study was to investigate comparatively in vitro the shear bond strength of conventional adhesive systems with and without collagen removal using 10 % sodium hypochlorite and self-etch adhesives. 48 human's molars were extracted for surgery and orthodontic reasons and after cleaning, they were stored in freezers (-18º C). The teeth were sectioned in an axial plan (mesio-distal), separated in two halves, vestibular and lingual. The teeth were mounted in self-cure resin and the labial and lingual surfaces were ground with sequential abrasive sandpaper to standardize the smear layer and expose the dentin with 2 mm of the thickness. The adhesion surface was delimited in 3 mm of diameter, the specimens were separated into six groups in accordance with adhesive system and dentin treatment: OBF - self-etch adhesive One-Up Bond F (Tokuyama); CSEB- self-etch primer Clearfil SE Bond (Kuraray); SB - Single Bond (3M); SBMP - Scotchbond Multi Uso Plus (3M); SBH - after acid etching was used at 10% sodium hypochlorite (AD Gel - Kuraray) during one minute and then Single Bond was used; SBMPH - after the acid etching sodium hypochlorite at 10% was used (AD GelKuraray) during one minute and then Scotchbond Multi Uso Plus was used. The composite resin Z-100 (3M) was inserted by incremental technique with a metallic matrix on a prepared surface. The shear test was realized in an lnstron Universal machine at 0,5 mm/min speed. The fractured surfaces were classified in stereomicroscopic (Karl Zeiss). The data obtained was analyzed by ANOVA and Tukey tests. The data showed the following values (in MPa): CSEB- 24,362; SB- 20,956; SBH - 17,825; OBF - 17,355; SBMP - 17,218; SBMPH- 14,169. We concluded that self-etch adhesive CSEB showed bond strength significantly higher than OBF and SBMP adhesives; the self-etch adhesive with acidificate primer showed bond strength statistically higher than where...

O objetivo deste estudo foi avaliar comparativamente, in vitro, a resistência adesiva ao cisalhamento de sistemas adesivos convencionais come sem a remocão do colágeno com hipoclorito de sódio a 10% e adesivos autocondicionantes. Utilizou-se 48 molares humanos extraídos por indicacão cirúrgica ou ortodôntica que, após a limpeza, foram armazenados em freezer a -18°C. Os dentes foram seccionados em urn plano axial mésio-distal separando-os em duas metades, vestibular e lingual. Após o embutimento em resina acrílica, tiveram as superfícies vestibular e lingual desgastadas com lixa numa sequência de granulacão decrescente para padronizar a smear layer e expor a dentina até a espessura de 2 mm. A área de adesão foi delimitada em 3 mm de diâmetro. Os espécimes foram divididos em seis grupos, de acordo com o sistema adesivo e o tratamento dentinário realizado: OBF - adesivo autocondicionante One-Up Bond F (Tokuyama); CSEB - primer autocondicionante Clearfil SE Bond (Kuraray); SB -Single Bond (3M); SBMP - Scotchbond Multi Uso Plus (3M); SBH – após o condicionamento ácido foi utilizado o hipoclorito de sódio a 10% (AD Gel - Kuraray) durante um minuto e em seguida utilizado o Single Bond; SBMPH - após o condicionamento ácido foi utilizado o hipoclorito de sódio a 10% (AD Gel - Kuraray) durante um minuto e, em seguida, utilizado o Scotchbond Multi Uso Plus. A resina composta Z-100 (3M) foi inserida pela técnica incremental, em matriz metálica, sobre a área preparada. 0 ensaio mecânico de cisalhamento foi realizado em uma máquina lnstron Universal à velocidade de 0,5 mm/min. As superfícies fraturadas foram analisadas em estereomicroscópio (Karl Zeiss). Os dados foram submetidos à análise estatística, empregando-se os testes ANOVA e Tukey. Os resultados demonstraram os seguintes valores em MPa: CSEB - 24,362; SB - 20,956; SBH- 17,825; OBF - 17,355; SBMP - 17,218; SBMPH-14,169. Concluimos que...
Keywords: Cisalhamento; Adesivos dentarios; Materiais dentários; Dental materials